The Impact of Peer SSIAL Support on Bullying Behavior in Adolescents - Akmaaliyah, Ahdiyah Ziidah; Suminar, Ervi; Zuhro, Diah Fauzia; Fitrianur, Widya Lita (INNOVATION RESEARCH JOURNAL, 2024)
Background: The large number of bullying cases that occur every year causes anxiety and becomes the focus of attention of society and the government. The aim of the research was to determine the relationship between peer social support and bullying behavior among adolescents in MA. Ma'arif NU Sidomukti Gresik. Method: This research uses quantitative methods with a cross sectional approach. A population of 80 teenagers, 67 samples were studied using random sampling techniques. The instruments used in this research were the Social Provisions Scale (SPS) and OBQ questionnaires using the chi-square test. Results: The research results showed that the majority of students had high peer social support, 43 (64.2%). Half of the students did not behave bullying, 39 (58.2%). Based on the results of the chi-square test, it is proven that the p-value of 0.490 is above 0.05 (0.490>0.05. Conclusion: There is no relationship between peer social support and bullying behavior in MA. Ma'arif NU Sidomukti Gresik. Even though there is no relationship, the school and teachers should still monitor the activities carried out by students who do not take any problems lightly and follow up on these problems so that bullying behavior does not occur. Keywords : Peer Social Support, Bullying Behavior.